ANALYSIS OF NICKEL MINING ACTIVITIES IMPACT AT WATERSHED HIDROLOGY DISTRICT KOLAKA. - Bakri, Edy
According to data from the Directorate General of Mineral and Coal Ministry of Energy, Mining License number before Autonomous Region (1945-1999) is ± 600, while after Autonomous Region Mining Permit Number increased to 10 918 (February 3, 2014 status). Nickel mining in Kolaka generally using open pit methods (surface mining). The use of surface mining method has the potential to change the form of topographic and land cover, thus affecting the hydrological conditions in the river basin and watershed of Huko Huko and Oko-Oko. Results of Landsat image processing at 2015 is known that the wide opening of the mine in Huko-Huko watershed is ± 1986 Ha. Oko-Oko watershed while reaches ± 4080 Ha. These conditions underlying the research done on the impact of mining on the hydrological conditions. The method used is TopModel, Data physical characteristics of the watershed input in analyzing changes in the hydrological conditions include nine parameters, namely; T0 (transmissivity maximum), K0 (Hydraulic conductivity of saturated), M (constant discharge), DRZ init (Initial Root Zone Storage), DRZ max (Maximum Allowable Root Zone Storage) Td (Vertical Time Delay), Vr (Channel Routing Velocity) , CD (capillary Drive), and qs_init (Initial Subsurface (Groundwater) Flow). The results of modeling reveals that the maximum precipitation of 0.04547 mm / hour average discharge in the watershed Huko-Huko with natural conditions (undisturbed) is 5:19 m3 / sec while the peak discharge amounted to 12.79 m3 / sec. The average discharge of the river in the watershed that has been disturbed at 7:35 m3 / sec, while the peak discharge is 23:47 m3 / sec. So the increase in fluctuations in river discharge between before land clearing and after the opening of the area is 83.5%, while the DAS Oko-Oko with maximum precipitation of 0.04547 mm / hour, peak discharge on the condition of natural amounted to 45.33 m3 / sec, while the discharge the average of 8.69 m3 / sec. Peak discharge after a disturbed is amounting to 55.62 m3 / sec and the average discharge is 12.69 m3 / sec. So the increase in river discharge fluctuations between before and after their mining mining amounted to 22.7% To prevent the occurrence of hydrological disaster such as flooding and siltation of the river it is necessary to prevention efforts, including improvement of governance IUP.